SPIRITUAL AND EDUCATIONAL EVENTS ANALYSIS AND THEIR RESULTS IN HIGHER EDUCATIONAL INSTITUTIONS OF PEDAGOGY IN UZBEKISTAN DURING THE INDEPENDENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the pedagogical direction of Uzbekistan in the spiritual and educational work in higher education institutions, a series of events organized for students to spend their free time meaningfully, roundtables, meetings with experts on topical issues, the role and importance of spiritual and educational activities in training teachers information on achievements, problems and their solution analysis.